2020
DOI: 10.2337/dc19-0806
|View full text |Cite
|
Sign up to set email alerts
|

Genetic Susceptibility Determines β-Cell Function and Fasting Glycemia Trajectories Throughout Childhood: A 12-Year Cohort Study (EarlyBird 76)

Abstract: Genetic susceptibility determines -cell function and fasting glycaemia trajectories throughout childhood: a 12-yr cohort study (EARLYBIRD 76).

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
9
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 19 publications
(13 citation statements)
references
References 34 publications
3
9
1
Order By: Relevance
“…Thus, rs12970134 may reflect susceptibility to more extreme HbA1c elevation. This finding is consistent with recent data from the EarlyBird cohort, where the rs12970134 A‐allele was associated with 12‐year fasting glucose trajectory >75th percentile in healthy children, but not associated when a 50th percentile cut‐point was examined 28 …”
Section: Discussionsupporting
confidence: 92%
“…Thus, rs12970134 may reflect susceptibility to more extreme HbA1c elevation. This finding is consistent with recent data from the EarlyBird cohort, where the rs12970134 A‐allele was associated with 12‐year fasting glucose trajectory >75th percentile in healthy children, but not associated when a 50th percentile cut‐point was examined 28 …”
Section: Discussionsupporting
confidence: 92%
“…Weight gain and obesity further exacerbate the physiological insulin resistance of puberty and fasting glycemia, and will favor atherogenic changes in the lipid profile and pathways, such as one carbon metabolism. This is in line with our other findings which suggested that weight gain and increasing insulin resistance will exacerbate hyperglycaemia ( 15 ) in adolescence, especially in those who also have genetic impairment of pancreatic beta cell function ( 13 , 15 ).…”
Section: Discussionsupporting
confidence: 93%
“…The children who developed IFG already exhibited higher fasting blood glucose levels at 5 years of age, compared with those who did not subsequently develop IFG, and this effect was independent of BMI ( 12 ). Recently, we reported that the occurrence of an early defect in β-cell function among children who go on to develop prediabetes ( 12 ), was genetically determined and independent of BMI ( 13 ). These studies also revealed how genetic markers are associated with normal glycemic trajectories during childhood.…”
Section: Introductionmentioning
confidence: 99%
“…5). Recent work from the EarlyBird cohort demonstrated that genetic markers associated with type 2 diabetes in adults are also present in youths [105]. These markers were more commonly associated with beta cell dysfunction and increasing glucose, independent of BMI or insulin resistance.…”
Section: Areas For Future Workmentioning
confidence: 99%